A Study of Project Management Processes for Sustainable and Successful Projects in Software Industry: Expectations vs Perceptions of Managers - Ashfaq Ahmad; Muhammad Bilal; Khalid Latif; Zainab (Journal of Accounting and Finance in Emerging Economies, 2021)
Project Management Processes (PMPs) are essential to avoid project failures due to the complexity and nature of projects in the software industry, particularly in emerging economies. The software industry is growing rapidly in Pakistan with an increasing number of local, regional and international clients. The project managers who are familiar with PMPs are therefore needed for the proper implementation of these processes, which will lead to sustainable and successful software projects. However, very limited studies have analyzed the expectations and perceptions of the project managers of these PMPs. In order to fill this gap, therefore, this study examined the role of PMPs in the sustainable development and success of software projects by documenting the expectations and perceptions of managers. A structured questionnaire is designed to collect data from 143 participants working in software houses. SPSS is used for the processing and analysis of data using selected statistical tools. The results show a clear difference in expectations and perceptions for PMPs, which means that project managers are of a less rational, sentimental and emotional nature. The findings of this study also show that the male segment is dominant in the software industry which may be due to of Pakistan’s specific social and cultural environment. There is however no significant difference between expectations and perceptions of both male and female project managers for PMPs. The findings of this study will help researchers, practitioners, academics and other stakeholders in the software industry.